Migration orientations of teachers and student teachers in Albania: a sequential mixed-methods study - Plaku, Anila Koli; Thanasi, Teuta (Frontiers in Education, 2025)
IntroductionThis study explores the migration orientations of in-service teachers and student teachers in Albania, a country facing persistent educational and labor market challenges within the Western Balkans. Teacher attrition and outward migration have intensified debates on retention, professional status, and education system sustainability.MethodsA sequential exploratory mixed-methods design was employed. Qualitative data collected in 2023 identified key push and pull factors, such as low salaries, limited professional development, and declining recognition of the profession, which informed the development of a nationwide survey administered to 816 participants in 2025.ResultsQuantitative analyses showed no significant associations between migration intentions and economic status, age, or perceived professional status. However, a clear group difference emerged: student teachers were more frequently undecided about emigration, whereas in-service teachers expressed clearer intentions either to stay or to leave. Qualitative narratives provided deeper insight, emphasizing the interplay of economic pressures, institutional weaknesses, and concerns related to professional dignity and trust.DiscussionFindings highlight the limitations of partial reforms and underscore the need for systemic measures that strengthen professional recognition, career pathways, and institutional credibility. The study offers longitudinal evidence that contributes to debates on teacher retention and education sustainability, with implications for policy strategies aimed at reducing teacher shortages in transitional education systems and advancing the Sustainable Development Goals.